REDUCTION OF AVERTABLE LOSS OF HEALTH IN CHILDREN - THE STRATEGY OF SOCIAL PEDIATRICS - A.A. Baranov; T.V. Yakovleva; V.Yu. Al'bitsky; A.A. Modestov; E.V. Antonova ("Paediatrician" Publishers LLC, 2008)
The basic trends of development of social pediatrics are described in this article. The main attention was given to investigations, favored to the reduction of loss of children's health related to morbidity and disablement, which can be eliminated with appropriate medical care and prophylactic measures, and mortality of children. This measures have to be based on proper public health politics. Key words: social pediatrics, health, prophylaxis.